Răspuns:
Cel mai simplu e babeste, dupa regula:
[tex](a-b)^3=a^3-3a^2b+3ab^2-b^3[/tex]
Atunci: [tex](1-i\sqrt 3)^3 = 1 - 3(i\sqrt 3) + 3(i\sqrt 3)^2 - (i\sqrt 3)^3 = 1 - 3\sqrt 3 i + 3\cdot (-3) + 3\sqrt 3 i = 1 - 9 = -8 [/tex].
Se poate face si cu forma trigonometrica:
Fie [tex]z=1-i \sqrt 3[/tex]. Atunci [tex]|z|=\sqrt{1+(\sqrt 3)^2}=\sqrt{1+3}=\sqrt 4 = 2[/tex]. Deci
[tex]z=2(\frac{1}{2}-\frac{\sqrt{3}}{2}i) = 2(\cos \frac{\pi}{3} - i \sin \frac{\pi}{3} )[/tex]
Rezulta ca [tex]z^3 = 8 (\cos \pi - i \sin \pi) = 8\cdot(-1) = - 8[/tex].